2019
DOI: 10.31235/osf.io/a6cfy
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wag the dog - The nature and foundations of preschool educators' positive ICT pedagogical beliefs

Abstract: It has become evident that the vast majority of early childhood educators feel positive about using ICT with children. However, as they are found to have had no or only a little training or practical experience of pedagogical use of ICT, it is important to explore where the positive attitude comes from, and what pedagogical benefits early childhood educators believe ICT use brings about. This study focuses on the relationships of educators' general and ICT-related pedagogical beliefs, and the foundations of ed… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…English language teachers with the ICT integration have tried to determine the ICT skills of English language teachers in the light of existing infrastructure facilities to promote English language teaching and learning. Mertala (2017) found that to choose and use the right ICT tools at the right time, teachers must be prepared for learning about new tools, organizing in-class and out-of-class activities, guiding and monitoring students' engagement in online activities for evaluating students' learning performance. Pedagogical beliefs can be influenced positively based on the perceptions of learners towards different ICT devices and software in terms of their use in English language learning procedure.…”
Section: Pedagogical Implications Of Ict Toolsmentioning
confidence: 99%
“…English language teachers with the ICT integration have tried to determine the ICT skills of English language teachers in the light of existing infrastructure facilities to promote English language teaching and learning. Mertala (2017) found that to choose and use the right ICT tools at the right time, teachers must be prepared for learning about new tools, organizing in-class and out-of-class activities, guiding and monitoring students' engagement in online activities for evaluating students' learning performance. Pedagogical beliefs can be influenced positively based on the perceptions of learners towards different ICT devices and software in terms of their use in English language learning procedure.…”
Section: Pedagogical Implications Of Ict Toolsmentioning
confidence: 99%
“…As with other teacher beliefs, pedagogical beliefs serve as “an intuitive screen” (Goodman, 1988, p. 130) that sifts new information and events and affect teachers’ various instructional decisions in classrooms, including activity structure, teacher‐student interactions, flexible grouping practices and technology use (Blay & Ireson, 2009; Ertmer, 2005; Lee, Zhang, Song, & Huang, 2013). It is commonly agreed in the field that pedagogical beliefs comprise two major dimensions: traditional (teacher‐centered) and constructivist (student‐centered) beliefs (Hermans, Tondeur, & van Braak, 2008; Liu, 2011; Mertala, 2017). Teachers who hold traditional beliefs tend to see themselves as the source of knowledge and emphasize behavioral engagement, knowledge transmission and passive learning in classrooms.…”
Section: Theoretical Underpinningsmentioning
confidence: 99%
“…Also, the vast majority of educators, with little or no training or practical experience in the pedagogical use of ICT, are still pleased to use ICT with their learners. This optimistic ICT pedagogical attitudes were mainly based on perceptions of what specific student learning devices and applications promise and offer (Mertala, 2017).…”
Section: Introductionmentioning
confidence: 99%